Matching and Money - Corbae, Dean; Temzelides, Ted; Wright, Randall (American Economic Review, 2002)
In Corbae, Temzelides, and Wright (2001) (hereafter, CTW) we proposed a new version of the framework that uses bilateral matching to model the exchange process, and in particular to model the use of money as a medium of exchange. Our version does not have agents meeting exogenously and at random, but rather has agents meeting endogenously. That is, agents are matched at each date subject to a stability condition that requires, roughly, that no agents prefer to be paired with each other or to be unmatched, rather than to be paired with the partners they get along the equilibrium path. While similar in spirit to the cooperative matching concept introduced by David Gale and Lloyd Shapley (1962), we had to generalize their framework to dynamic models because we are interested in monetary economics. Here we present a version of the solution concept in CTW, specialized in some ways but also generalized to include extrinsic uncertainty (sunspots). We then discuss some applications of endogenous matching models to issues that have previously been addressed using random matching, including the existence of sunspot equilibria and the efficiency of inside versus outside money. One of our main goals is to show how endogenous matching is a useful alternative to random matching. This may be interesting to those who think that bilateral trade is a reasonable friction upon which to build a theoretical foundation for monetary economics but perhaps think that random matching is an extreme and unrealistic simplification. Another goal is to provide examples where it makes a difference for substantive results how we model the matching process, and also examples where it does not. I. Endogenous Matching